1995
DOI: 10.1152/jappl.1995.79.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Microdialyzed adenosine in nucleus tractus solitarii and ventilatory response to hypoxia in piglets

Abstract: Levels of adenosine, inosine, and hypoxanthine from the interstitial space at the nucleus tractus solitarii were measured by microdialysis in eight 20- to 25-day-old anesthetized spontaneously breathing piglets. Microdialyzed samples were collected every 30 min for 2 h after the insertion of the probe to ensure stability of purine levels and then during 30 min each of normoxia, hypoxia (10% O2-90% N2), and normoxia. The purines were separated by high-pressure liquid chromatography with ultraviolet detection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…In both situations, decreases in MAP are accompanied by decreases in HR and RSNA and sustained increases in pre-ASNA (34,35,44). The similarities between the patterns of the responses may be physiologically relevant because adenosine is released into the central nervous system, including the NTS, during hypoxia, ischemia, and severe hemorrhage (26,43,46). Consistent with this concept, our preliminary data showed that blockade of adenosine receptors attenuates the bradycardic and sympathoinhibitory responses to severe hemorrhage (38).…”
mentioning
confidence: 61%
“…In both situations, decreases in MAP are accompanied by decreases in HR and RSNA and sustained increases in pre-ASNA (34,35,44). The similarities between the patterns of the responses may be physiologically relevant because adenosine is released into the central nervous system, including the NTS, during hypoxia, ischemia, and severe hemorrhage (26,43,46). Consistent with this concept, our preliminary data showed that blockade of adenosine receptors attenuates the bradycardic and sympathoinhibitory responses to severe hemorrhage (38).…”
mentioning
confidence: 61%
“…In respiratory networks, adenosine is clinically significant because it depresses ventilation (Herlenius et al, 1997;Herlenius and Lagercrantz, 1999;Mironov et al, 1999), and is implicated in the hypoxia-induced depression of ventilation (Yan et al, 1995) and apnea in newborns (Runold et al, 1989;Lopes et al, 1994). Our observation that the post-ATP decrease in frequency depends on ATP breakdown suggests that effects of ATP on rhythm will be determined by an interaction between P2 and P1 receptors.…”
Section: Implication Of Atp Hydrolysismentioning
confidence: 81%
“…The primary natural source of adenosine is ATP released from nerve terminals and glial cells, which is subsequently catabolized to adenosine by ectonucleotidases (46,63,74). Importantly, adenosine is also released into extracellular space during life-threatening homeostasis imbalance such as hypoxia, ischemia, and severe hemorrhage; in these pathological situations adenosine results from massive catabolism of intracellular ATP (45,61, 69,72,73). Inasmuch as the most basic, life-supporting, reflexes (cardiovascular, respiratory, and other autonomic reflexes) are primarily integrated in the NTS (17), it is not surprising that the greatest density of adenosine uptake sites in the entire central nervous system is located in the NTS (6).…”
mentioning
confidence: 99%